The Outer Circle: Models of Association for Non-Members (EEA, Switzerland, UK, Turkey) - Tubić, Bojan (Unequal Equals? The Status of Member States in an Integrating European Union, 2026)
This chapter explores the various alternatives to direct involvement in the European Union international framework, particularly concerning the European Economic Area (hereinafter: EEA). The principle of homogeneity, which underpins the EEA’s functioning, is critically analysed in terms of its implications for non-EU countries seeking integration with EU markets while maintaining sovereignty. The relationship between the EU and Turkey is examined, with a focus on the complex dynamics of Turkey’s customs union and its aspirations for full EU membership. Additionally, the chapter investigates the deep and comprehensive free trade areas between the EU and countries such as Moldova, Georgia, and Ukraine, analysing how these agreements serve as tools for economic and political integration without full EU membership. Lastly, the post-Brexit relationship between the EU and the UK is discussed, highlighting the intricacies of trade agreements, regulatory alignment, and the ongoing political and economic negotiations that define this new phase of European cooperation. By examining these multifaceted relationships, the chapter aims to provide insights into the evolving dynamics of European integration and the alternatives to EU membership for countries and regions within its sphere of influence.